C-Reactive Protein Knockout Attenuates Temporomandibular Joint Inflammation in Rats. (10th January 2022) - He, Yao; Zhou, Mengjiao; Jian, Zixiang; Fang, Lingli; Huang, Lan; Song, Jinlin
Abstract : Background . C-reactive protein (CRP), a biomarker of inflammation, is highly expressed in osteoarthritis- (OA-) related diseases, but its exact role remains unknown. In this study, we evaluated the biological effect of CRP on temporomandibular joint (TMJ) inflammation. Methods . Freund's complete adjuvant (CFA) was used to induce TMJ inflammation in CRP-knockout (CRP-/-) and control rats. Degenerative changes in the TMJ were compared to elucidate the role of CRP in TMJ inflammation. In addition, inflammatory cytokines, macrophage activation, and osteoclast differentiation were evaluated by real-time quantitative polymerase chain reaction, immunohistochemistry, and tartrate-resistant phosphatase staining to explore the potential regulatory mechanism. Results . Compared to the control, CFA induced TMJ inflammation, which increased systemic and local CRP expression. Furthermore, CRP-/- rats exhibited less severe inflammatory symptoms. The downregulation of proinflammatory cytokines (interleukin- (IL-) 1 β and IL-6) and upregulation of the anti-inflammatory cytokine IL-10 were detected in CRP-/- rats, which also exhibited reduced macrophage activation and osteoclast differentiation. Conclusion . These results indicated that controlling the highly elevated levels of CRP during inflammation could modify the cytokine profile, macrophage activation, and osteoclast differentiation, thus, providing beneficial effects for TMJ-OA prevention and treatment.